1990
DOI: 10.1148/radiology.174.2.2404320
|View full text |Cite
|
Sign up to set email alerts
|

Radionuclide bone imaging in the early detection of fractures of the proximal femur (hip): multifactorial analysis.

Abstract: The results of 179 radionuclide bone imaging examinations, 105 gathered retrospectively from the cases of 97 patients referred for assessment of possible occult fracture of the proximal femur (hip) and 74 performed prospectively on 63 patients referred with a diagnosis of obvious or suspected hip fracture, were analyzed in relation to patient age, the interval between injury and imaging, and the type of fracture sustained. Ninety-two examinations were performed less than 72 hours after injury; 31 of these were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
43
0
1

Year Published

1991
1991
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(44 citation statements)
references
References 0 publications
0
43
0
1
Order By: Relevance
“…One large study by Holder et al of 179 hip scans established a sensitivity of 93.3% for scintigraphy (35). When patients who had obvious fractures on X-ray were removed from analysis, leaving 145 with normal or equivocal X-rays, the sensitivity of scintigraphy increased to 97.8% (35). A similar sensitivity of 97.6% was found by Lewis et al in a study of 82 patients (36).…”
Section: Bone Scanningmentioning
confidence: 65%
See 1 more Smart Citation
“…One large study by Holder et al of 179 hip scans established a sensitivity of 93.3% for scintigraphy (35). When patients who had obvious fractures on X-ray were removed from analysis, leaving 145 with normal or equivocal X-rays, the sensitivity of scintigraphy increased to 97.8% (35). A similar sensitivity of 97.6% was found by Lewis et al in a study of 82 patients (36).…”
Section: Bone Scanningmentioning
confidence: 65%
“…It may, however, be considered an alternative to MRI if patients are admitted. One large study by Holder et al of 179 hip scans established a sensitivity of 93.3% for scintigraphy (35). When patients who had obvious fractures on X-ray were removed from analysis, leaving 145 with normal or equivocal X-rays, the sensitivity of scintigraphy increased to 97.8% (35).…”
Section: Bone Scanningmentioning
confidence: 99%
“…Patients with radiographic findings that were only suggestive of fracture or were normal were excluded. Holder et al [6] also recognized the importance of early diagnosis of hip fractures in the elderly. Their thorough study of 175 patients with known or suspected hip fractures on bone scans found no false positive or false negative studies in patients below the age of 69 years.…”
Section: Discussionmentioning
confidence: 99%
“…26 Although magnetic resonance imaging (MRI) is universally recognized as the gold standard for diagnosing the occult hip fracture, 13,27 with sensitivity and specificity approaching 100%, 20,[28][29][30][31] earlier studies used either clinical progression or bone scanning for diagnosis. 19,[22][23][24] Bone scanning, or bone scintigraphy, has a reported sensitivity and specificity of 93% and 95%, respectively 32 ; however, it is thought to take 24 to 72 hours for a scan to become positive in older patients. Other drawbacks of this modality are that it may not delineate the full extent of the fracture line 20 and the recent inconsistent availability of the substrate radionuclide material used to perform the examination.…”
Section: Discussionmentioning
confidence: 99%